The Meaning of Thaharah in Al-Quran (Semantic Analysis by Toshihiko Izutsu) - Amanah, Afrina Zulfah Nur; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
The word thaharah is a word that is heard very often. In the Qur'an the word thaharah has different contexts. The aim of this research is to find out the meaning of the word thaharah, which is often mentioned in the Qur'an. Each verse that contains the word thaharah has a different meaning so a deep understanding is needed to find out. The method that will be used in this research is the semantic method proposed by Toshihiko Izutsu. The word thaharah means holy, clean. The opposite of thaharah is menstruation or uncleanness. Syntagmatically, the relational meaning of thaharah has the meaning of bathing and giving alms. Meanwhile, paradigmatically thaharah has the same meaning as zaka and qaddasa, the opposite words are najis and menstruation. Historically the word thaharah is divided into several parts or periods. First, the word thaharah is pre-Quranic, which tends to have a spiritual meaning, where thaharah is defined as purity of heart and morals; secondly, the Qur'anic period has a more developed meaning, namely spiritual and external purity or protecting oneself from all uncleanness and hadats.